A functional polymorphism of the microRNA-146a gene is associated with susceptibility to drug-resistant epilepsy and seizures frequency. (April 2015) - Cui, Lili; Tao, Hua; Wang, Yan; Liu, Zhou; Xu, Zhien; Zhou, Haihong; Cai, Yujie; Yao, Lifen; Chen, Beichu; Liang, Wandong; Liu, Yu; Cheng, Wanwen; et al.
Highlights: The association between miR146a polymorphisms and epilepsy was explored. An association between the rs57095329 SNP and DRE was found. The rs57095329 A allele was associated with a reduced seizure frequency. Abstract: Purpose: Epilepsy is the third most common chronic brain disorder and is characterized by an enduring predisposition for seizures. Recently, a growing body of evidence has suggested that microRNA-146a (miR-146a) is upregulated in the brains of epilepsy patients and of mouse models; furthermore, miR-146a may be involved in the development and progression of seizures through the regulation of inflammation and immune responses. In this report, we performed a case–control study to analyze the relationship between the two potentially functional single nucleotide polymorphisms (SNPs) of the miR-146a gene (rs2910464 and rs57095329) and the risk of epilepsy in a Chinese population comprising 249 cases and 249 healthy controls. Method: Our study comprised 249 epilepsy patients and 249 healthy controls in two regions of China. The DNA was genotyped using the ABI PRISM SNapShot method. The statistical analysis was estimated using the chi-square test or Fisher's exact test. Results: Our results indicated a significant association between the rs57095329 SNP of the miR-146a gene and the risk of drug resistant epilepsy (DRE) (genotypes, p = 0.0258 and alleles, p = 0.0108). Moreover, the rs57095329 A allele was found to be associated with a reduced risk of seizures frequency in DRE patients (all p < 0.001). However, the rs2910164 variant was not associated with epilepsy. Conclusion: Our data indicate that the rs57095329 polymorphism in the promoter region of miR-146a is involved in the genetic susceptibility to DRE and the seizures frequency.